Application of the Promotion and Retirement Determination ProcessAt the Desktop-Based Directorate of Sabhara Polda North Sumatra - Eka Rahayu; Tantri Hidayati Sinaga; Arie Rafika Dewi (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
In the administrative process for information on the rank and retirement of personnel from the Sabhara Directorate of the North Sumatra Regional Police, they still apply a manual system, where personnel must know when they will be promoted or retired, resulting in personnel neglect due to too much work. The promotion and retirement process takes a long time, because it requires consideration and approval from the leadership. From this problem, the author applies a system for determining the promotion and retirement process at the North Sumatra directorate automatically with notifications (alarms) for personnel who will be promoted and retired based on a desktop with Windows operating system. This application was created to assist the North Sumatra Regional Police Directorate in processing rank and pension data from members of the police quickly and accurately, to realize smooth operations..